A scalable electrodeposition route to the low-cost, versatile and controllable fabrication of perovskite solar cells. (July 2015) - Chen, Haining; Wei, Zhanhua; Zheng, Xiaoli; Yang, Shihe
Abstract: Hybrid organic/inorganic perovskite solar cells (PSCs) have emerged as a highly promising alternative renewable energy source because of their high efficiency and low-cost solution processable manufacturing technology. However, the commonly used spin coating process limits the large-scale manufacturing of perovskite layers for commercialization. Here we report on the development of an electrodeposition technique for fabricating perovskite layers and demonstrate its simplicity, versatility, scalability and roll-to-roll manufacturing compatibility. The key step is the electrodeposition of a PbO2 layer on TiO2 scaffold, which is then subjected to chemical bath conversion to sequentially generate PbI2 and CH3 NH3 PbI3 perovskite. Clearly demonstrated is the controllability of morphology and optical properties of the CH3 NH3 PbI3 layer, leading to a higher power conversion efficiency (PCE) reproducibility and a higher average PCE when incorporated into carbon-based PSCs than with the spin coating technique. Remarkably, the cell area of electrodeposited PSCs could be easily scaled up to 4 cm 2 with an excellent perovskite film uniformity, rendering a PCE gain of 36.3% over the spin-coated counterpart. We further demonstrate the deposition of perovskite layers on complex shape substrates (e.g., stainless steel net), which would be rather difficult or impossible with other competing film deposition techniques. These results establish electrodeposition as a versatile and controllable route toward low-cost and large scalable manufacturing of high efficiency PSCs. Graphical abstract: Highlights: An electrodeposition route is exploited to fabricate high-quality perovskite layer. Electrodeposited device achieves a higher average efficiency than spin-coated counterpart. Large-area electrodeposited device is much more efficient than spin-coated counterpart. The whole route is cost effective, versatile and compatible with roll-to-roll production line.